2018
DOI: 10.1126/sciadv.aao5498
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis reveals the mechanism of transcription activation in M. tuberculosis

Abstract: Mycobacterial activator RbpA stimulates transcription by stabilizing open conformation of the RNA polymerase σ subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 41 publications
6
28
0
Order By: Relevance
“…Based on the similarities between the effects of RbpA and of the TGTG motif on transcription, we propose that RbpA could strengthen the interaction of the σ subunit domains 3 and 4 with promoter DNA upstream of the −10 element. This hypothesis is supported by our smFRET study showing that σ B in the Mtb RNAP holoenzyme adopts a conformation incompatible with binding to −10/-35 promoters and that RbpA stabilizes σ B in a conformation compatible with binding ( 27 ). The finding that σ4 was still required for transcription initiation in the context of the extended −10 sin P3 and sig AP-TGTG promoters even in the presence of RbpA suggests that σ4 may have additional roles in initiation, probably in organizing RNAP clamp or β subunit flap domains for RPo formation, as proposed for E. coli σ 70 ( 44 ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Based on the similarities between the effects of RbpA and of the TGTG motif on transcription, we propose that RbpA could strengthen the interaction of the σ subunit domains 3 and 4 with promoter DNA upstream of the −10 element. This hypothesis is supported by our smFRET study showing that σ B in the Mtb RNAP holoenzyme adopts a conformation incompatible with binding to −10/-35 promoters and that RbpA stabilizes σ B in a conformation compatible with binding ( 27 ). The finding that σ4 was still required for transcription initiation in the context of the extended −10 sin P3 and sig AP-TGTG promoters even in the presence of RbpA suggests that σ4 may have additional roles in initiation, probably in organizing RNAP clamp or β subunit flap domains for RPo formation, as proposed for E. coli σ 70 ( 44 ).…”
Section: Discussionsupporting
confidence: 59%
“…Recently, we demonstrated that RbpA stabilizes the ‘open’ conformation of the σ B subunit in Mtb RNAP. This is optimal for recognition of the −10/-35 promoters, but is dispensable for recognition of the extended −10 promoters ( 27 ). Here, to better understand the molecular basis of this promoter specificity, we explored the effect of mutations in σ B and RbpA on Mtb RNAP activity at promoter variants that harbor different combinations of the extended −10 and −35 motifs.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the s subunit anti-pausing activity can be observed with RNAP from other bacteria, we studied initial transcription by MtbRNAP. We used the M. tuberculosis s B subunit that requires the activator protein RbpA to stabilize its active conformation in the MtbRNAP holoenzyme (Vishwakarma et al, 2018). As RbpA N-terminus binds within the RNA-exit channel, it could modulate s4.2 anti-pausing activity (model in Fig.…”
Section: Rbpa From M Tuberculosis Stimulates Translocation Through Tmentioning
confidence: 99%
“…Binding of the regions s3.2 and s4.1 within the RNA exit channel takes place during assembly of the RNAP holoenzyme when the s subunit undergoes the transition from the "closed" to the "open" conformation (Callaci et al, 1999). Recent single-molecule fluorescence resonance energy transfer studies demonstrated that in Mycobacterium tuberculosis, this transition is regulated by the activator protein RbpA (Vishwakarma et al, 2018) that interacts with the s2 and s3.2 domains (Boyaci et al, 2018). Whether RbpA can influence initial transcription has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Data from structural and biophysical studies suggest that free group 1 and 2 σ subunits adopt a "closed" inactive conformation in which the spatial arrangement of domains σ2 and σ4 is incompatible with promoter DNA binding. Binding to core RNAP induces or stabilizes an "open, " active σ conformation, optimal for promoter binding (Callaci et al, 1999;Schwartz et al, 2008;Vishwakarma et al, 2018). Canonically, RNAP activity at promoters is regulated through DNA-binding transcription factors (Browning and Busby, 2016) that recognize and bind to specific motifs on dsDNA (DB-TFs) and influence the initiation pathway steps after promoter binding ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%